Does Pricing Strategy Increase the Competitive Advantage of Companies Implementing an ABC System? - Devie, Devie; Kwistianus, Hendri; Antonia, Aileen Jessica; Wijaya, Elizabeth; Hatane, Saarce Elsye (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2022)
Abstract. This study aims to investigate the extent to which pricing strategy creates an effective competitive advantage for companies implementing an activity-based costing (ABC) system in their production activities. The research data were obtained through a questionnaire-based survey of several manufacturing companies in Indonesia that implement ABC systems. This research used the Structural Equation Model with Partial Least Square statistical method. The results of this research indicate that those companies who apply an ABC system are capable of making their pricing strategy more effective and increasing their competitive advantage. The empirical results show that price competition is unavoidable among manufacturing industries. However, implementing an ABC system can increase manufacturing companies' competitive advantage. Thus, the implementation of an ABC System employs pricing strategy as a determinant factor of competitive advantage. This research supports the results of previous studies that also concluded that there is a strong relationship between ABC systems and competitive advantage. In addition, this research found that pricing strategy can improve competitive advantage with implementation of an ABC System.Keywords: Activity-based costing system; competitive advantage; pricing strategy Abstrak. Studi ini bertujuan untuk menginvestigasi sejauh mana Strategi Penetapan Harga mampu menciptakan Keunggulan Bersaing yang efektif bagi perusahaan yang menerapkan Sistem Activity Based Costing dalam kegiatan produksinya. Data dalam penelitian ini didapatkan menggunakan survei berbasis kuesioner dari perusahaan manufaktur di Indonesia yang menerapkan Sistem Activity Based Costing. Penelitian ini akan menggunakan Structural Equation Model (SEM) dengan metode statistic Partial Least Square. Hasil penelitian ini menunjukkan bahwa perusahaan yang menerapkan Sistem Activity Based Costing terbukti mampu membuat Strategi Penetapan Harga perusahaan lebih efektif dan sekaligus berdampak pada peningkatan Keunggulan Bersaing. Hasil empiris menunjukkan bahwa persaingan harga tidak dapat dihindari dalam industri manufaktur. Tetapi, dengan menerapkan Sistem Activity Based Costing, perusahaan manufaktur mampu meningkatkan Keunggulan Bersaing. Sehingga, kehadiran Sistem Activity Based Costing menjadi Strategi Penetapan Harga sebagai penentu Keunggulan Bersaing. Penelitian ini memperkuat hasil penelitian sebelumnya yang juga menyimpulkan bahwa ada hubungan yang kuat antara Sistem Activity Based Costing dan Keunggulan Bersaing. Dalam penelitian ini, juga menemukan kesimpulan bahwa Strategi Penetapan Harga mampu meningkatkan Keunggulan Bersaing melalui implementasi Sistem Activity Based Costing.Kata kunci: Sistem activity based costing; keunggulan bersaing; strategi penetapan harga.